The Role of Islamic Preachers in Developing Social Harmony and Civilization in South Sumatera in the 20th Century - Nurseri Hasnah Nasution (Proceedings of International Conference on Da'wa and Communication, 2019)
In the XXth Century, the da’wa problems that emerged in South Sumatra were the spread of fundamentalism and the cult of persona, the diversity of religious articulations, the vulnerability in the internal environment of religious communities, the plurality of political, social, and religious atmosphere so that they became polemic among academicians, the clergy split into two groups, changes in religious traditions and religious life that are complex, the Muslims of South Sumatra are in position of weakness, poverty, and suffering, because of western imperialism, issues of justice, ideology, and power. Some preachers (Da,i)in South Sumatra appeared to respond and carry out the Da’wa bi al-lisanl, bi al-kitabah, and bi al-hal. Among the preachers (da’i) are K.H. Anwar Kumpul (1902-1959) represented an independent preacher (free), K.H. Zainal Abidin Fikry represents the government representative, K.H. M. Zen Syukri represents a representative of the NU organization. These three preachers (da’i) are actively building social harmony in different societies of educational and economic status, religious harmony, building an orderly, peaceful, and comfortable society, stopping the people of South Sumatra from making God and Islam as masks of the greed of power and material wealth, glue various differences in society and make it a means for mutual understanding, tolerance, and mutual love. In addition, they also play role in building theoretical and experimental civilizations which include ideas, norms, religious activities, establishing places of worship, educational institutions, libraries, roads, and producing books.